2015
DOI: 10.11607/ofph.1383
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence and Toothache of Adolescents from Southern Brazil

Abstract: The results of this study showed that a strong SOC protected against toothache. A health-promotion approach may lead to better patterns of oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In addition, in the present study, 32.5% reported having suffered toothache in the last 6 months, similar time to results found by other authors, such as Schuch et al 4 in Pelotas, RS, where the prevalence of dental pain was of 35.7%, and Noro et al .26 , made in Sobral, CE, where the prevalence of toothache was 31.8% in the last 6 months. This prevalence should be considered high when compared to the following studies: Freire et al 27 performed in 26 capitals of Brazilian states and in the Federal District, where the prevalence of toothache was 17.8%; Jaiswal et al 28 , in Kollipara Mandal, Guntur district, Andhra Pradesh, India, whose prevalence of toothache was 28.3%; Rosa et al 29 , performed in 36 municipalities with up to 50,000 inhabitants in Rio Grande do Sul, where 29.8% reported having toothache in the last 6 months. In turn, it is inferior to the results of the study carried out in Santa Maria, RS, where they found a prevalence of toothache in the last 6 months in 63.2% of students 30 and in Leh, Ladakh, India, which showed that the prevalence of pain in the last 6 months was 77% 31 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, in the present study, 32.5% reported having suffered toothache in the last 6 months, similar time to results found by other authors, such as Schuch et al 4 in Pelotas, RS, where the prevalence of dental pain was of 35.7%, and Noro et al .26 , made in Sobral, CE, where the prevalence of toothache was 31.8% in the last 6 months. This prevalence should be considered high when compared to the following studies: Freire et al 27 performed in 26 capitals of Brazilian states and in the Federal District, where the prevalence of toothache was 17.8%; Jaiswal et al 28 , in Kollipara Mandal, Guntur district, Andhra Pradesh, India, whose prevalence of toothache was 28.3%; Rosa et al 29 , performed in 36 municipalities with up to 50,000 inhabitants in Rio Grande do Sul, where 29.8% reported having toothache in the last 6 months. In turn, it is inferior to the results of the study carried out in Santa Maria, RS, where they found a prevalence of toothache in the last 6 months in 63.2% of students 30 and in Leh, Ladakh, India, which showed that the prevalence of pain in the last 6 months was 77% 31 .…”
Section: Discussionmentioning
confidence: 92%
“…caries not treated as being of African descent, from public schools, with income equal to or less than a minimum wage and living in housing with a high family density. The study by Rosa et al 29 conducted in 36 municipalities with up to 50,000 inhabitants in Rio Grande do Sul, showed that adolescents with dental caries reported having up to twice as much toothache as those without dental caries. Authors describe that quality of life related to oral health and dental pain was associated with school absenteeism in 12-yearold adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os demais seis estudos nacionais mostraram um α de Cronbach aceitável para a escala inteira, variando de α = 0,67 a α = 0,80 para a versão com 13 itens [27][28][29][30][31][32] , e valores de α = 0,78 e α = 0,87 para SOC-29, em dois estudos 21,24 . Para validação de conteúdo, nenhuma pesquisa submeteu os itens das escalas a uma revisão por membros da população alvo através de grupos focais.…”
Section: Resultsunclassified
“…The predictive role of SOC for adolescents' long‐term mental health has also been highlighted (Grevenstein et al, 2016). Higher SOC has also been associated with lower dental anxiety (Carlsson et al, 2015), better patterns of oral health (Da Rosa et al, 2015; Lage et al, 2017), better perceived general oral health and lower rates of periodontal disease (Cyrino et al, 2016) and predicted levels of dental caries (Viswanath & Krishna, 2015) and a positive perception of dental aesthetics (Aline Cavalcanti Da et al, 2017). SOC was also associated with a better social life and networking (Anmyr et al, 2015) and was positively associated with life satisfaction (Moksnes & Haugan, 2015), self‐rated health (Nunes, 2017) and self‐esteem (Moksnes & Lazarewicz, 2016).…”
Section: Discussionmentioning
confidence: 99%